Ni3S2@MoO3@Co3O4@AMO/NF core–shell heterostructure for high performance alkaline overall water splitting - Jiabang Liang; Yu Liu; Zegao Wang; Yifan Jia; Zhao Ding; Liangjuan Gao (Discover Nano)
Abstract The urgent need for bi-functional high-performance non-noble metal-based catalysts for water splitting requires the integration of both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) together, which not only increases the energy efficiency but also reduces fabrication cost. However, most non-noble metal-based catalysts for OER are not stable under alkaline conditions, while HER shows poor kinetic performance under alkaline conditions, which prevents the water splitting from scale-up applications. Therefore, in this paper, non-noble metal-based catalyst of Ni3S2@MoO3@Co3O4@AMO/NF was prepared by a two-step hydrothermal method followed by a galvanic replacement reaction with morphological characterization, demonstrating that the synthesized material has a core–shell structure. The electrochemical properties of Ni3S2@MoO3@Co3O4@AMO/NF were tested and analyzed, which confirmed its efficient electrocatalytic activity. The catalyst exhibited excellent OER in 1 M KOH solution, and a low overpotential of 248 mV was achieved at a current density of 10 mA cm−2. In addition, the catalyst maintained competitively low overpotentials even at high current densities, 281 mV and 303 mV at 50 mA cm−2 and 100 mA cm−2, respectively. Remarkably, only an overpotential of 185 mV was required to reach the current density of 10 mA cm−2 for HER. The excellent OER and HER performances could be attributed to the synergistic effects among AMO, Co3O4 and MoO3. In addition, Ni3S2@MoO3@Co3O4@AMO/NF required only 1.414 V at 10 mA cm−2 to complete the overall water splitting and exhibited excellent competitiveness also at high current densities (1.769 V and 1.975 V at 50 mA cm−2 and 100 mA cm−2, respectively). The morphology of Ni3S2@MoO3@Co3O4@AMO remained stable after long time i-t tests, which proved its long-term operational stability. The Faraday efficiencies of the OER and HER could reach 75.92% and 97.51%, respectively, which showed excellent electrocatalytic performance. Therefore, the synthesis of high-performance bifunctional catalysts based on a two-step hydrothermal reaction followed by a galvanic replacement reaction proposed in this study provides a new strategy for the simple and efficient synthesis of non-noble metal-based catalysts for high-performance overall water splitting.